Sensitivity of power losses in electric energy system branches on disturbances in nodes - Lezhniuk, P. D.; Lesko, V. O. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Method of sensitivity evaluation of total power losses in electric energy system as the criterion of its modes optimality and power losses in separate branches of electric networks to load changes in nodes is suggested, the given method allows to determine optimal sequence of corrective influences on electric system modes.